(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Traditional herbal medicine remains dominant to women’s healthcare due to its accessibility, affordability and cultural acceptance. This study documented and quantitatively analysed medicinal plants used for women’s health and reproductive care among rural communities of Idukki district, Kerala. Ethnobotanical data were collected exclusively from women informants using semi-structured interviews, field observations and identifying women as the primary guardians of reproductive health knowledge. A total of 42 medicinal plant species belonging to 29 families were recorded, with major use for menstrual disorders and postnatal care. Use Value and Fidelity Level analyses revealed the culturally important multipurpose species and ailment-specific remedies. The study highlights under-documented traditional knowledge and highlights the need for conservation and scientific validation of key medicinal plants.